Prospects of USM-drivers use in two-coordinate coelostat design - Davletov, Askar; Shakirov, A.L. (Recent Contributions to Physics, 2015)
The aim of the study is to develop a model of two-coordinate coelostat with USM- drivers. A theoretical model of the device was designed. The optical scheme includes a telescope with a two-coordinate coelostat mounted at the entry and consisting of two units including diagonal mirrors and USM- drivers. Finding of the object, setting and driving may be performed automatically by the computer. The studies revealed highly promising prospects of USM- drivers application in this design. A working dummy based on the Maksutov lens was developed and constructed. The technique of work in azimuthal, equatorial, horizontal and periscopal operation was tested. Two-coordinate coelostat with USM- drivers may find application in large telescopes, including space and mercury ones.